2011 5th International Conference on Bioinformatics and Biomedical Engineering 2011
DOI: 10.1109/icbbe.2011.5780451
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Fibrillation Detection Based on Empirical Mode Decomposition

Abstract: Automatic detection of ventricular fibrillation (VF) is of great important for automated external defibrillators (AEDs). However, it is a difficult issue due to the similarity between ventricular fibrillation and ventricular tachycardia (VT). In this paper, a novel scheme based on empirical mode decomposition (EMD) is proposed to disclosure the underlying information of VT, VF and normal electrocardiogram (ECG). The intrinsic mode functions (IMFs), especially the first IMF, may demonstrate distinct properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…During the long-term analysis, a high classification accuracy of 88.5% was achieved for VT vs. VF classification. This was in alignment with previous works that attempted to solve the same problem [8,15]. Unlike previous approaches that utilized decomposition techniques predicated on the choice of a pre-defined basis function, the EMD algorithm decomposes the data into IMFs based on the inherent properties of the data itself.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…During the long-term analysis, a high classification accuracy of 88.5% was achieved for VT vs. VF classification. This was in alignment with previous works that attempted to solve the same problem [8,15]. Unlike previous approaches that utilized decomposition techniques predicated on the choice of a pre-defined basis function, the EMD algorithm decomposes the data into IMFs based on the inherent properties of the data itself.…”
Section: Discussionsupporting
confidence: 62%
“…Bai et al also performed classification of NSR, VT, and VF using and EMD based approach [15]. They were also able to achieve a high classification accuracy for discriminating those 3 rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elias Ebrahimzadeh et.al [4] had shown that better accuracy was obtained by using both the time-frequency and nonlinear features. Hence in this paper, two non-linear features are chosen, namely 'Spectral Entropy' [17] and 'Lyapunov Exponent' [18] to extract the most distinctive properties of the signal. A positive lyapunov exponent points that the system could be chaotic [8].…”
Section: Feature Extraction and Classificationmentioning
confidence: 99%
“…The standard deviations of the peak amplitudes and peak distances in a cross correlation between a window of ECG and a short window immediately prior is used to classify VT from VF in [9]. An algorithm for VF detection based on empirical mode decomposition (EMD), which creates a lower dimensional representation of ECG waveforms based on the energy in the first EMD component and its spectral entropy, was proposed in [10]. Counting the time between ECG turning points was proposed [11] to differentiate fast-VT, slow-VT and VF for use in automatic implantable cardiovertor defibrillators (AICDs).…”
Section: Introductionmentioning
confidence: 99%